Insect pollination of sulla (Hedysarum coronarium L.) and its effect on seed production in a Mediterranean environment - Satta A.; Acciaro M.; Floris I.; Lentini A.; Sulas L. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
During the flowering period of 1998, insect pollinators of two varieties of Hedysarum coronarium L. (Grimaldi and Sparacia) were monitored in an area of Northern Sardinia (Italy). The Apidae Apis mellifera L. and the Anthophoridae Eucera numida Lep. were the main pollinators. Among the seed yield components, the number of loments per raceme and seeds per loments were 98 per cent and 42 per cent lower, respectively, in the absence of pollinators in Grimaldi. The percentage of flowers setting seed was about 50 per cent in both varieties, even though the mean number of pollinators per flower was 1.4 fold higher in Grimaldi than in Sparacia.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)